Combining methods for non-invasive fecal DNA enables whole genome and metagenomic analyses in wildlife biology - de Flamingh, Alida; Ishida, Yasuko; Pečnerová, Patrícia; Vilchis, Sahara; Siegismund, Hans R.; van Aarde, Rudi J.; Malhi, Ripan S.; Roca, Alfred L. (Frontiers in Genetics, 2023)
Non-invasive biological samples benefit studies that investigate rare, elusive, endangered, and/or dangerous species. Integrating genomic techniques that use non-invasive biological sampling with advances in computational approaches can benefit and inform wildlife conservation and management. We use non-invasive fecal DNA samples to generate low- to medium-coverage genomes (e.g., >90% of the complete nuclear genome at 6 X-fold coverage) and metagenomic sequences, combining widely available and accessible DNA collection cards with commonly used DNA extraction and library building approaches. DNA preservation cards are easy to transport and can be stored non-refrigerated, avoiding cumbersome and/or costly sample methods. The genomic library construction and shotgun sequencing approach did not require enrichment or targeted DNA amplification. The utility and potential of the generated data generated was demonstrated through of genome-scale analysis and metagenomics of zoo and free-ranging African savanna elephants (Loxodonta africana). Fecal samples collected from free-ranging individuals contained an average of 12.41% (5.54-21.65%) endogenous elephant DNA. Clustering of these elephants with others from the same geographic region was demonstrated by a principal component analysis of genetic variation using nuclear genome-wide SNPs. Metagenomic analyses generated compositional taxon classifications that included Loxodonta, green plants, fungi, arthropods, bacteria, viruses and archaea, showcasing the utility of this approach for addressing complementary questions based on host-associated DNA, e.g., pathogen and parasite identification. The molecular and bioinformatic analyses presented here contributes towards the expansion and application of genomic techniques to conservation science and practice.